2022
DOI: 10.1186/s13018-022-03115-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotics versus personalized 3D preoperative planning in total knee arthroplasty: a propensity score-matched analysis

Abstract: Purpose Lower limb alignment is crucial in total knee arthroplasty (TKA). Previous studies have shown that robotics and personalized three-dimensional (3D) preoperative planning could improve postoperative alignment accuracy compared with conventional TKA, but comparison between the above two techniques has never been reported. The authors hypothesized that robotics may be superior to personalized 3D preoperative planning in terms of postoperative alignment in primary TKA, with similar patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Various digital technologies for orthopaedic surgeries, such as navigation, robot-assisted surgery, and PSI, have been used to improve the accuracy of component placement. Navigation and robot-assisted surgery can significantly improve surgical accuracy, but they are also disadvantageous in that they are expensive and prolong the operation time, so their generalizability is somewhat limited [14,15]. There is still controversy regarding the use of PSI in improving the accuracy of component alignment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various digital technologies for orthopaedic surgeries, such as navigation, robot-assisted surgery, and PSI, have been used to improve the accuracy of component placement. Navigation and robot-assisted surgery can significantly improve surgical accuracy, but they are also disadvantageous in that they are expensive and prolong the operation time, so their generalizability is somewhat limited [14,15]. There is still controversy regarding the use of PSI in improving the accuracy of component alignment.…”
Section: Discussionmentioning
confidence: 99%
“…With a basis in CT-based preoperative planning, digital technologies, such as navigation, robot-assisted techniques, and patient-specific instrumentation (PSI), are being used in arthroplasty [14][15][16]. All these techniques have been reported to improve surgical accuracy, but navigation and robotic technologies require costly purchases and maintenance, increase the operating time, and require additional, sufficiently large spaces for application and storage.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this study use these options: using press-fit implants instead of cement automatically because they increase the surgical site incision, using Deaver and selfretaining retractors, and having a low threshold to release the gluteus maximus or psoas tendon or an anterior capsulectomy. Generally, the authors avoid minimally invasive approaches and are judicious about the use of robotics, as this will ultimately lengthen the procedure [20]. In the operating room, multidisciplinary teams, orthopaedic-specific surgical assistants, and decreasing operative room turnover can improve operative room cohesion and efficiency [5,15].…”
Section: Effect Of Operative Time On Obesity-related Riskmentioning
confidence: 99%
“…One certain benefit of RA-TKA, which can decrease surgical trauma, is the avoidance of femoral medullary canal invasion. Most authors have reported that intraoperative and postoperative blood loss in RA-TKA is always significantly less [ 11 ]. The invaded femoral canal could bleed severely during surgery and be responsible for undetectable blood loss after surgery.…”
Section: Factors That Can Decrease Surgical Trauma Of Ra-tkamentioning
confidence: 99%